INTEGRATING LOCAL CONTEXT TO TEACHING ENGLISH FOR YOUNG LEARNERS (EYL) - Dedi Irwansyah (Jurnal Pedagogy, 2013)
English for young learners (EYL) studies have dealt with quiet number of teaching methods and strategies. However, researchers have not conducted adequate analyses of EYL teacher candidates‟ creativity in integrating the local context into their lesson plans. This writing, therefore, address this issue by analyzing the teacher candidates‟ portfolio when they take English for Children course. Limitation of accessibility, however, have led this study to only focus on analyzing the portfolios submitted by the teacher candidates pursuing their S1 degree in an English Language Teaching Department of State Islamic College of Metro Lampung, Indonesia. This study will contribute to filling the gap of the stakeholders‟ expectation toward the possibility of integrating the local context, particularly Islamic values as they are the prominent characteristic of the college, into the arena of ELT within Indonesian context. The analysis shows that local and ideological features are inseparable in ELT and that those are commonly integrated with songs and pictures.